Performance of Halal Certification Policies in East Java Province - Nawangsari, Ertien Rining; Yusuf, Rima Ranitya; Adnin, Hani Nur; Anggoro, Dicky (Future Science, 2023)
Halal certification serves as evidence of the safety of products for both Muslim and non-Muslim communities, particularly in Indonesia, where the majority of the population adheres to Islamic principles. The presence of halal product certification ensures fairness, legal certainty, protection, transparency, and professionalism in the approval of a product. Therefore, the government needs to continue its efforts in supporting industrial products to obtain halal certification. Nevertheless, numerous small and medium-sized enterprises (SMEs) still lack halal certification for their products. This research aims to evaluate the performance of the halal certification policies in East Java, focusing on output indicators such as coverage, bias, accessibility, program strategies, and alignment with the target requirements. This study employs a mixed-method approach, utilizing primary data gathered through questionnaires, interviews, and on-site observations within East Java Province, with a sample size of 400 out of a total business unit population of 820,005. The findings indicate that, in terms of coverage, 42.3% of respondents have reservations about complying with the halal certification policy. Concerning bias, 46% of respondents believe that the policy does not sufficiently address the needs of SMEs. As for accessibility, 36.8% of respondents reported difficulties in accessing the halal certification policy.